Pertussis Disease and Antenatal Vaccine Effectiveness in Australian Children. Issue 3 (March 2022) - Quinn, Helen E.; Comeau, Jeannette L.; Marshall, Helen S.; Elliott, Elizabeth J.; Crawford, Nigel W.; Blyth, Christopher C.; Kynaston, Jennifer A.; Snelling, Tom L.; Richmond, Peter C.; Francis, Joshua R.; Macartney, Kristine K.; McIntyre, Peter B.; et al.
Abstract : Background: Population-level studies of severe pertussis extending beyond infancy are sparse, and none in the context of antenatal vaccination. We compared hospitalized pertussis cases from birth to 15 years of age before and after introduction of antenatal immunization. Methods: Active surveillance of laboratory-confirmed pertussis hospitalizations in a national network of pediatric hospitals in Australia January 2012 to June 2019. Impact of maternal vaccination was assessed by vaccine effectiveness (VE) in cases and test-negative controls with <2 months of age and by before-after comparison of age distribution of cases. Among cases eligible for one or more vaccine doses, we examined proportions age-appropriately immunized and with comorbidities by age group. Results: Among 419 eligible cases, the proportion <2 months of age significantly decreased from 33.1% in 2012 to 2014 compared with 19.6% in 2016 to 2019 when mothers of only 4 of 17 (23.5%) cases <2 months of age had received antenatal vaccination. VE was estimated to be 84.3% (95% CI, 26.1–96.7). Across all years (2012–2019), of 55 cases 4–11 months of age, 21 (38%) had ≥2 vaccine doses, whereas among 155 cases ≥12 months of age, 122 (85.2%) had ≥3 vaccine doses. Prevalence of comorbidities (primarily cardiorespiratory) increased from 5 (2.1%) <6 months of age to 36 (24.2%) ≥12 months of age ( P < 0.001), with 6/16 (38%) cases ≥12 months of age who required intensive care having comorbidities. Conclusions: Below the age of 12 months, prevention of severe pertussis will be maximized by high maternal antenatal vaccine uptake and timeliness of infant vaccine doses. Despite full immunization, we found children ≥12 months of age accounted for 27% of hospitalizations <15 years, with 24% having comorbities, suggesting new vaccine strategies, such as additional doses or more immunogenic vaccines, require evaluation.